Clinical pharmacy and therapeutics - Walker, Roger; Whittlesea, Cate. (Edinburgh ; New York : Churchill Livingstone, 2007)
A practical guide for the treatment of common diseases, this updated edition includes the very latest information. It covers the treatment of disease by drug therapy and uses case studies to illustrate the application of the principles discussed
Section 1: General Clinical pharmacy process. Prescribing. Practical pharmacokinetics. Drug interactions. Adverse drug reactions. Laboratory data. Parenteral nutrition. Pharmacokinetics. Section 2: Life stages Neonates. Paediatrics. Geriatrics. Section 3: Therapeutics Gastrointestinal disorders: Peptic ulcer disease. Inflammatory bowel disease. Constipation and diarrhoea. Hepatic disorders:Adverse effects of drugs on the liver. Liver disease. Renal disorders: Chronic kidney disease and end-stage renal failure. Acute renal failure. Cardiovascular disorders: Hypertension. Coronary heart disease. Chronic heart failure. Cardiac arrhythmias. Thrombosis. Dyslipidaemia. Respiratory disorders: Asthma. Chronic obstructive pulmonary disease. Drug-induced lung disease. Neurological and psychological disorders: Insomnia and anxiety. Affective disorders. Schizophrenia. Epilepsy. Parkinson's disease. Pain. Nausea and vomiting. Infections: Respiratory infections. Urinary tract infections. Gastrointestinal infections. Infective meningitis. Surgical antibiotic prophylaxis. Tuberculosis. HIV infection. Fungal infections. Endocrine disorders: Thyroid and parathyroid disorders. Diabetes mellitus. Obstetric and gynaecological disorders: Menstrual cycle disorders. Menopause. Drugs in pregnancy and lactation. Urological disorders: Benign prostatic hyperplasia. Haemotopoietic disorders: Anaemia. Malignant disorders: Leukaemia. Lymphomas. Solid tumours. Rheumatic disorders: Rheumatoid arthritis and osteoarthritis. Gout and hyperuricaemia. Eye disorders: Glaucoma. Skin disorders: Drug-induced skin disorders. Eczema and psoriasis. Pressure sores and leg ulcers. Section 4: Appendices. Medical abbreviations. Glossary. Index
Includes bibliographical references and index.
Keywords: Chemotherapy; Pharmacology; Therapeutics; Pharmacy; Drug Therapy; Pharmacology, Clinical